2008
DOI: 10.1108/09534810810856435
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transformational leadership on organizational innovation and performance depending on the level of organizational learning in the pharmaceutical sector

Abstract: PurposeThis empirical study aims to examine the influence of transformational leadership (TL) on organizational innovation (OI) and performance (OP) depending on the level of organizational learning in technological firms.Design/methodology/approachThe research examined a sample of 164 pharmaceutical firms. A global model is formulated and the hypotheses are tested using structural equations.FindingsFirst, the study shows a positive relation between TL and OI, between TL and OP and between OI and OP. Second, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
0
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(141 citation statements)
references
References 75 publications
5
121
0
15
Order By: Relevance
“…Leadership style and human resources both have a positive relationship with achieving organizational innovation [76,77]. Many other studies also argue that leadership is positively linked to organizational innovation [78][79][80].…”
Section: Managerial Capability and Organizational Innovationmentioning
confidence: 99%
“…Leadership style and human resources both have a positive relationship with achieving organizational innovation [76,77]. Many other studies also argue that leadership is positively linked to organizational innovation [78][79][80].…”
Section: Managerial Capability and Organizational Innovationmentioning
confidence: 99%
“…For example, in dynamic industries such as pharmaceuticals, electronics, biotechnology and IT, product innovation is essential which demands organizations for continuous product development in order to succeed in the intense competition and fast product evolution environment. These types of industries are considered as research intensive industries that adopt indicators such as Research and Development (R&D) expenditures and capital investments, publications and patents as the common measures for innovation [18].…”
Section: Innovation In Construction Industrymentioning
confidence: 99%
“…Many scholars have endorsed the importance of innovation in determining the performance of an organization [8,18,44,47,48]. These studies were done across different economic sectors around the globe and relate innovation to industries' performance that further recognized the importance of innovation for an economy's success.…”
Section: The Relationship Between Innovation and Organizational Perfomentioning
confidence: 99%
See 1 more Smart Citation
“…The same idea was advocated by Wang and Wang (2012) who claimed that explicit and tacit knowledge sharing is positively linked to innovation speed and quality. Garcia-Morales et al (2008) suggested also that innovation is the result of combination of existing knowledge and generation of new knowledge. Cantner et al (2011) highlighted the importance of knowledge management in companies" innovative success.…”
Section: Introductionmentioning
confidence: 99%